Bundle 4: Mechanization: Progress Update: Partner Workplan 2024 - Matin, Abdul; Mulundu, Stephen (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This report presents a progress update on the mechanization bundle. In collaboration with National Association of Smallholder Farmers, the project has identified three potential mechanization service providers in Chongwe district and these are two females and one male. Youth in the area, particularly those in vegetable production and chicken rearing, will be benefiting from the services to provided by the service providers. The equipment include two tractors, shellers and planter. The SMEs are given equipment and demostrate the use of equipment to farmers.